1. LIQUID BIOPSY- A NEW PROSPECT (Iraqi Journal of Medical Sciences, 2019)
Tissue biopsy has been the mainstay in tumor diagnosis for centuries. But due to its invasiveness and the heterogeneity of tumors there was a need for an alternative or adjuvant techniques to diagnose and assess tumors. Liquid biopsy is emerging as a new technique that will open the way for the diagnosis, tumor characterization, assess disease prognosis and individualize treatment options in cancer patients.Keywords:Biopsy, CTC, ctDNACitation: Mahdi AK. Liquid biopsy - A new prospect. Iraqi JMS. 2018; 16(4): 353-356. doi: 10.22578/IJMS.16.4.1
Keywords: Biopsy; CTC; ctDNA